Shapin, Steven, A social History of Truth. Civility and Science in Seventeenth-century England, Chicago y Londres, The University of Chicago Press, 1994. - Buch, Alfonso (Universidad Nacional de Quilmes, 1996)
Fil: Buch, Alfonso. Universidad Nacional de Quilmes. Centro de Estudios e Investigaciones; Argentina.